THE APPLICATION OF MIDWIFERY CARE TO REDUCE DISCOMFORT CAUSED BY FREQUENT URINATION IN THIRD-TRIMESTER PREGNANT WOMEN AT THE MITRA HUSADA CLINIC IN MEDAN IN 2026 - Masnia Gultom; Retno Wahyuni; Maria Indani; Repi Mariska; Alya Armalia (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
ABSTRACT Background: Frequent urination is a physiological discomfort experienced during the third trimester due to mechanical pressure from the fetal head, which reduces bladder capacity by up to 50%. If left untreated, this condition can lead to insomnia and increase the risk of urinary tract infections (UTIs). Objective: To implement and evaluate comprehensive midwifery care to reduce the discomfort of frequent urination in third-trimester pregnant women at the Mitra Husada Clinic in Medan in 2026. Methods: This study employed a descriptive case study design, utilizing Helen Varney’s 7-Step Midwifery Care Management and SOAP documentation. The study subject was Mrs. M, G1P0A0, at 31 weeks of gestation, who complained of frequent urination. The intervention was conducted over 14 days and included nighttime fluid restriction (the 8-2-1 regimen), the double voiding method, and self-administered Kegel exercises. Data were analyzed descriptively and comparatively. Results: Objective evaluation showed significant changes after two weeks of intervention. The frequency of nighttime urination (nocturia) decreased from an average of 8.5 ± 0.5 times to 3.0 ± 0.2 times per night. Effective sleep duration increased from an average of 4.0 ± 0.5 hours to 7.0 ± 0.5 hours without any complaints of physical fatigue. Clinical evaluation also showed no symptoms of urinary tract infection (UTI). Conclusion: The implementation of midwifery care based on Helen Varney’s 7-step approach-which focuses on adjusting fluid intake and strengthening the pelvic floor muscles-has been shown to be effective in reducing the frequency of urination and optimizing sleep quality in pregnant women in their third trimester.